Identités collectives ; territoires et mémoires - Sylvie Contrepois (Conserveries Mémorielles)
To what extent do attempts to preserve local memory help highlight the ways contemporary societies change ? This question is at the core of a European research project on the historical and contemporary articulations of regional, national and European identities through work and community in areas undergoing economic restructuring and regeneration (SPHERE : www.sphereeurope.eu). The project’s methods include regional advisory groups in each of the country partner and important efforts to disseminate the results to local citizens.The area studied in France is located in the Paris suburbs and is composed of two adjacent urban areas (“communautés d’agglomérations”), one being Evry and the other Corbeil-Essonnes. The first symbolises the services era and the urban renewal brought by new towns. The second retains traces from a really important industrial past. Focusing the study on them both together creates a good opportunity to analyse continuities and discontinuities in changes in work and social identities.The French advisory board is composed of the presidents of four local history and memory associations. For the first time, the data produced by each of those associations are confrontedand analysed together, along with the data produced by the researcher. This paper analyses this approach and its results.